Inhibition activity of Robusta coffee beans polyphenol extract on the production of TNF-α neutrophil cells - Tantin Ermawati; Zahara Meilawaty; Happy Harmono (Faculty of Dentistry, Universitas Gadjah Mada, 2018)
Polyphenols are one of the active substances in the Robusta coffee beans with various benefits for humans’ health including anti-inflammation. neutrophil cell (polymorphonuclear PMN) plays a significant role as the primary immune response against foreign agent. Inflammatory response is characterized by the production of pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α). Hence, the purpose of this study is to determine anti-inflammation capacity of Robusta coffee beans polyphenols extract on the TNF-α production in neutrophil cells. Neutrophil was derived from human peripheral venous blood by means of gradient density method. One hundred microliter of neutrophil (1,5x103 cell) was incubated with 3.13%, 6.25%, 12.5%, 25% polyphenol extract and exposed with 100 μl of Lipopolysaccharides (LPS) 25 mg/ml. The production of TNF-α were determined by ELISA. Data were analyzed by one way Anova. Polyphenols of Robusta coffee bean extract was shown to inhibit TNF-α production in LPS-exposed neutrophil cells compared to controls. Whereas, LPS-exposed neutrophil increased TNF-α production. The most effective concentration to inhibit TNF-α production was 12.5%. It was concluded that polyphenols of Robusta coffee beans has anti-inflammatory properties as indicated by its ability to decrease TNF-α levels.